Mitigation measures for critical factors causing cost overrun in Malaysian building projects - Ullah, Kaleem (2018)
Construction industry is one of the most important industries as it plays a vital role in the socio-economic growth of a country. However, construction industry faces severe problem of cost overrun. Like other countries, building projects in Malaysia are also affected by cost overrun. There are various factors contributing to cost overrun in building projects and it is vital to understand how they can be mitigated in order to improve cost performance in building project. Thus, the purpose of this study was to determine mitigation measures for critical factor causing cost overrun in Malaysian building projects. This study employed mixed method research covering both quantitative and qualitative approaches. A total of thirty six (36) factors causing cost overrun were identified from literature review. Based on these factors, a questionnaire survey was carried out to determine critical cost overrun factors. Results of the survey determined 31 critical factors causing cost overrun in building projects. Then, interview sessions with construction experts involved in handling of building projects were carried out to explore possible mitigation measures for each of the critical cost overrun factors. Finally, another questionnaire survey was conducted among construction experts to assess the level of significance of the mitigation measures. The findings from the survey showed the most significant mitigation for each critical cost overrun factors. For the top three critical cost overrun factors i.e. fluctuation in cost of materials, improper planning and scheduling and underestimate project duration, the most significant mitigation measures were establish applicable contract system with raw material suppliers, ensure effective planning at early stage of the construction project and appoint well skilled project planner respectively. This study would help the construction practitioners to apply specific measures to mitigate the critical factors that could possibly lead to the escalation of construction project cost. Thus, it will not only directly benefit the construction community, but also indirectly to the country economically.